Respuesta :

gmany

Answer:

[tex]\large\boxed{a_n=2(-4)^{n-1}=\dfrac{(-4)^n}{2}}[/tex]

Step-by-step explanation:

The explicit equation of a geometric sequence:

[tex]a_n=a_1r^{n-1}[/tex]

The domain is the set of all Counting Numbers.

We have the first term of [tex]a_1=2[/tex] and the second term of [tex]a_2=-8[/tex].

Calculate the common ratio r:

[tex]r=\dfrac{a_{n-1}}{a_2}\to r=\dfrac{a_2}{a_1}[/tex]

Substitute:

[tex]r=\dfrac{-8}{2}=-4[/tex]

[tex]a_n=(2)(-4)^{n-1}\qquad\text{use}\ \dfrac{a^n}{a^m}=a^{n-m}\\\\a_n=(2\!\!\!\!\diagup^1)\left(\dfrac{(-4)^n}{4\!\!\!\!\diagup_2}\right)\\\\a_n=\dfrac{(-4)^n}{2}[/tex]

Answer:

Step-by-step explanation:

A geometric sequence has a common ratio. in this case the common ratio

r = -8/2 = -4.

The explicit formula is an = 2(-4)^(n-1).

ACCESS MORE